2021
DOI: 10.1186/s13244-021-01101-7
|View full text |Cite
|
Sign up to set email alerts
|

The brainstem in multiple sclerosis: MR identification of tracts and nuclei damage

Abstract: Objective To evaluate the 3D Fast Gray Acquisition T1 Inversion Recovery (FGATIR) sequence for MRI identification of brainstem tracts and nuclei damage in multiple sclerosis (MS) patients. Methods From april to december 2020, 10 healthy volunteers and 50 patients with remitted-relapsing MS (58% female, mean age 36) underwent MR imaging in the Neuro-imaging department of the C.H.N.O. des Quinze-Vingts, Paris, France. MRI was achieved on a 3 T system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Nguyen et al further optimized brainstem imaging with a combination of FGATIR and PD/ T2w sequences to detect MS lesions down to the level of individual tracts and nuclei. [16] The inter-rater reliability of the MRI assessments among the three blinded neuroradiologists was only moderate, with a kappa coefficient of 0.58. While VOG can reliably distinguish the affected side, picking the affected side on MRI was difficult.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nguyen et al further optimized brainstem imaging with a combination of FGATIR and PD/ T2w sequences to detect MS lesions down to the level of individual tracts and nuclei. [16] The inter-rater reliability of the MRI assessments among the three blinded neuroradiologists was only moderate, with a kappa coefficient of 0.58. While VOG can reliably distinguish the affected side, picking the affected side on MRI was difficult.…”
Section: Discussionmentioning
confidence: 95%
“…Nguyen et al further optimized brainstem imaging with a combination of FGATIR and PD/T2w sequences to detect MS lesions down to the level of individual tracts and nuclei. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The brainstem nuclei and their neural networks perform a crucial role in regulating basic life-sustaining activities. Numerous previous articles have already reported that brainstem nuclei can be visualized using appropriate MRI sequences such as fast gray matter acquisition T1 inversion recovery, 3D-FLAIR, short tau inversion recovery, and so forth [ 2 , 3 , 23 27 ]. In this study, we used T1-MPRAGE and 3D-FLAIR as reference images for the averaged and individual 18 F-FDG PET images to facilitate recognition of which tracer accumulation corresponded to which brainstem nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…24 Prior MRI-based studies have revealed reduced brainstem cross-sectional areas in MS and the impact of involvement in relation to clinical outcomes. 25,26 In addition, newer techniques offer visualization of tracts and nuclei according to myelin density 27 and the importance of the spatial distribution of white matter lesions. 28 Reductions in pontine brain parenchymal fraction in pwMS with sexual dysfunction has also been reported.…”
Section: Discussionmentioning
confidence: 99%